MENINGKATKAN KECINTAAN SISWA TERHADAP AL-QURAN MELALUI PROGRAM TAHFIDZUL QUR’AN DI SMPN 4 PADANG PANJANG - Yuni Wulan Dari; Martin Kustati; Nana Sepriyanti (Jurnal Pengabdian Masyarakat Ilmu Keguruan dan Pendidikan (JPM-IKP), 2025)
This community service activity was motivated by the large number of students at SMPN 4 Padang Panjangwho could not read and did not even have memorized the Qur'an. Assistance in the Tahfizul Qur'anprogram uses the Service Learning approach. This approach is used to see the practices carried out by theTahfidzul Qur'an assistants to students at SMPN 4 Padang Panjang in reading and memorizing the Qur'an.The results of this service show that the Tahfidzul Qur'an program that was carried out had a positiveimpact and influence in improving memorization and reading of the Qur'an. However, there are still thingsthat need to be considered regarding students who do not participate in the tahfidz program on Thursday.Students who do not participate in the program are feared not to experience changes for the betterregarding reading the Qur'an and memorizing the Qur'an. The implications of service in the TahfidzulQur'a program include spiritual aspects, such as increasing spiritual awareness and deepeningrelationships with Allah SWT. Educational aspects, such as providing a holistic and integrative approach.Social aspects, such as being able to build students who have noble character and have awareness of moralvalues. And personal aspects, such as being able to improve memorization skills, strengthen memory, andbuild good character.